Implementation of Tri Hita Karana in Increasing Guest Satisfaction at Movenpick Resort & Spa Jimbaran Bali - I Kadek Surya Mardhitya; Ni Putu Lianda Ayu Puspita; Ni Made Rai Erawati; Elvira Septevany (Centre For Tourism Planning and Development, 2023)
This research aims to analyze the influence and efforts of the implementation of Tri Hita Karana in increasing guest satisfaction at Movenpick Resort & Spa Jimbaran Bali. Data collection methods used are observation and questionnaires. The number of respondents in this study amounted to 75 samples of guests staying overnight and one key informant using the incidental sampling method. The data analysis technique used is multiple linear regression analysis. Before the analysis, the validity and reliability tests were conducted on the questionnaires distributed to the respondents. Based on the results of the t-test that has been carried out, it is concluded that one independent variable partially has a negative influence and two independent variables have a positive influence in increasing guest satisfaction at Movenpick Resort & Spa Jimbaran Bali. The results of t-count evidence this> t-table, namely the Parahyangan variable of (-2.370) is greater than t-table (-1.667), the variable Pawongan of (4,242) is greater than t-table (1,667), and the Palemahan variable of (4,508) is greater than t-table (1,667). Based on the results of the F-test, the three independent variables simultaneously have a significant effect. It is evidenced by the significance value of F of 0.000 <0.05. With a significant influence on Tri Hita Karana implementation in increasing guest satisfaction, the Movenpick Resort & Spa Jimbaran Bali must further optimize the application. The hotel has tried to provide training on Tri Hita Karana to each employee so that employees can explain the meaning of Om Swastiastu greetings to guests. Besides that, Movenpick Resort & Spa Jimbaran Bali also has implemented digital-based services to increase guest satisfaction.